Federalism: Prospects for the Philippines - Romulo E.M. Miral (Philippine Institute for Development Studies (PIDS), 2017)
The paper aims to consider potential benefits of federalism to the Philippines within the context of two major development constraints, namely, weak economic growth and poverty. The governance and institutional aspects of these development constraints point to how continued centralization of fiscal powers and the resulting common resource pool problem have weakened government capacity to bring about inclusive development. Decentralization efforts, notably, the enactment of the Local Government Code and the establishment of the Autonomous Region for Muslim Mindanao, have not adequately reduced the common resource pool problem because of the failure to assign sufficient expenditure and revenue raising powers at the subnational levels. Aggravating factors include the overinvolvement of the national government in local government affairs, inadequate revenue raising powers of local governments, and over reliance of local governments to national government transfers, particularly the internal revenue allotment or IRA. Sound alternatives, on the other hand, include tax sharing, appropriate local taxation powers, an equalization transfer system, and a restructuring of IRA to address horizontal fiscal imbalance. Critical to the success of decentralization and fiscal federalism efforts is a strong middle level government, which is absent in the current setup. The establishment of regional governments, its powers and functions and its relation to the national government and local governments, is the most crucial element in the in the shift from a unitary to a federal form of government. It is recommended that the proposed shift be carried out in two stages. The first stage will deal with assignment of competencies and the relationship between the national government and regional government, with the power to organize the local governments being one of the competencies exclusively assigned to the latter. This shall be the task of the constituent assembly that will be constituted to propose amendments to the Philippine Constitution. The second stage will tackle the regional government and its local governments. Each regional government should come up with its own regional constitution or organic act that could be drafted through a regional constitutional convention.
Keywords: 330; Federalism; Decentralization; Autonomous Region; Local Government